The validation of forensic DNA extraction systems to utilize soil contaminated biological evidence. Issue 4 (July 2015) - Kasu, Mohaimin; Shires, Karen
Highlights DNA IQ effectively removes HA from highly contaminated blood and saliva. DNA IQ produces DNA of sufficient quality and quantity to generate full STR profiles. DNA IQ is highly recommended for use on soil-contaminated evidence. FTA-elute can be used for HA contaminated blood evidence. Nucleosave cards are not recommended for HA contaminated evidence.